2023
DOI: 10.1007/s00167-023-07350-x
|View full text |Cite
|
Sign up to set email alerts
|

A shallow morphology of the intertubercular groove is associated with medial and bilateral but not lateral pulley lesions

Abstract: Purpose To investigate the influence of intertubercular groove (IG) morphology on the development of different types of biceps reflection pulley (BRP) injuries. Methods A consecutive cohort of 221 patients with ventral shoulder pain and a preoperative diagnosis suspecting BRP injury, who underwent arthroscopy, was retrospectively reviewed. The presence or absence as well as type of pulley injury (medial, lateral or bilateral) was confirmed arthroscopically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…More than a decade earlier, Spritzer et al already postulated a strong correlation between ITG morphology and LHB tendon instabilities [27], limited by a small group size and lack of statistical analysis. Taking a closer look at LHB tendon instability and possible subsequent pathologies, Kleim et al analyzed different types of biceps reflection pulley (BRP) lesions on the basis of arthroscopy findings and showed that lateral BRP injuries are not influenced by the ITG morphology, whilst medial and bilateral ones are [28]. They presumed that a shallow BG morphology may lead to a dislocation of the LHBT, which may move out of the BG medially or laterally while external or internal rotation movement of the humerus subsequently damages the medial or lateral BRP [28].…”
Section: Intertubercular Groove Morphology and Its Influence On Lhb I...mentioning
confidence: 99%
See 1 more Smart Citation
“…More than a decade earlier, Spritzer et al already postulated a strong correlation between ITG morphology and LHB tendon instabilities [27], limited by a small group size and lack of statistical analysis. Taking a closer look at LHB tendon instability and possible subsequent pathologies, Kleim et al analyzed different types of biceps reflection pulley (BRP) lesions on the basis of arthroscopy findings and showed that lateral BRP injuries are not influenced by the ITG morphology, whilst medial and bilateral ones are [28]. They presumed that a shallow BG morphology may lead to a dislocation of the LHBT, which may move out of the BG medially or laterally while external or internal rotation movement of the humerus subsequently damages the medial or lateral BRP [28].…”
Section: Intertubercular Groove Morphology and Its Influence On Lhb I...mentioning
confidence: 99%
“…Taking a closer look at LHB tendon instability and possible subsequent pathologies, Kleim et al analyzed different types of biceps reflection pulley (BRP) lesions on the basis of arthroscopy findings and showed that lateral BRP injuries are not influenced by the ITG morphology, whilst medial and bilateral ones are [28]. They presumed that a shallow BG morphology may lead to a dislocation of the LHBT, which may move out of the BG medially or laterally while external or internal rotation movement of the humerus subsequently damages the medial or lateral BRP [28]. Looking at this "Skipping" of the LHB tendon out of the ITG, while rubbing over its rims from a pathophysiological viewpoint, it seems at least possible that the LHB tendon itself has a high probability of getting altered or inflamed the more often this dislocation occurs.…”
Section: Intertubercular Groove Morphology and Its Influence On Lhb I...mentioning
confidence: 99%